EdTech Promoting Social-Emotional Learning in India - Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
Social-emotional Learning, has been emerging as an effective process for cultivating the necessary skills, attitudes, competencies, and knowledge to learn and achieve well-being. These skills help to create a safe space for children to learn together and grow into an understanding and empathic adult. According to various researches, people with strong socio-emotional skills are better equipped to manage daily challenges, build positive relationships and make informed decisions. More than ever, students across the world report rising levels of anxiety and depression during the pandemic. In such difficult times, Educational Technology has played a major role and has been leveraged by the various educational communities to reach out to the students and make them feel less isolated. In the recent years , India has also seen a phenomenal shift in the approach where the focus of education is to develop human beings capable of rational thought and action, possessing compassion and empathy. The New education policy talks about socio-emotional learning for the holistic development of the child. Amid school closures, technology has been helping the educational communities to be in touch with the students with various platforms like WhatsApp, Video calling, Zoom, Google Classrooms, Radio, television, to be able to reach every part of the spectrum. In the Indian context, the lack of understanding of SEL and lack of necessary levers contextualizes SEL to the diverse environments is possibly the biggest challenge in adopting SEL practice. Together, collective actions towards integrating SEL into the education system will witness a new era of digital learning. It will be able to address all the core values which make us most human.
Keywords: 330